Birth Preparedness and Complication Readiness (BPCR) Among Women of Child Bearing Age (Medical Forum Monthly, 2024)
Objective: To determine the status of birth preparedness and complication readiness in relation to educational status of women of child bearing age group.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Indus Hospital (MSSH), Lahore from 1st January 2017 to 30th June 2017.Materials and Methods: This study comprised 384 delivered women. The socio-demographic characteristics, obstetric history, awareness of obstetric complication danger signs and practice of BPCR, and personal and social factors influencing the practice of BPCR were recorded.Results: Most of the women were in age group 26-35 years i.e. 211 (54.9%), education till matric had 201 (52.4%) women, housewives 338 (88%) and monthly income more than 15,000 per month i.e. 158 (41.2%) and 132 (34.4%) mothers were well prepared with mean BPCR score is 6.94±1.99.Conclusion: Most of the women in the study were not prepared for birth and its complications. However, highly educated women have better BP/CR score than less educated women.